Documentary photography reconsidered : history, theory and practice - Bogre, Michelle (London : Bloomsbury Visual Arts, 2019)
Documentary photography is undergoing an unprecedented transformation as it adapts to the impact of digital technology, social media and new distribution methods. In this book, photographer and educator Michelle Bogre contextualizes these changes by offering a historical, theoretical and practical perspective on documentary photography from its inception to the present day. Documentary Photography Reconsidered is structured around key concepts, such as the photograph as witness, as evidence, as memory, as narrative and as a vehicle for activism and social change. Chapters include in-depth interviews with some of the world's leading contemporary practitioners, demonstrating the wide variety of different working styles, techniques and topics available to new photographers entering the field. Every key concept is illustrated with work from a range of innovative, influential and often under-represented photographers, giving a flavor of the depth and range of projects from the history of this global art form. There are also creative projects designed to spark ideas and build skills, to help you conceive, develop and produce your own meaningful documentary projects.
Introduction -- 1. Reconsidering documentary photography -- 2. Documentary photography and memory -- 3. The documentary photograph as evidence -- 4. The photographer as witness -- 5. Narrative -- Appendix: Resources -- Bibliography -- Endnotes -- List of ilustrations -- Index.
Includes bibliographical references (pages 239-252) and index.
Keywords: Documentary photography; Documentary photography